Techno-Economic Optimization and Sensitivity Analysis of a Hybrid Grid-Connected Microgrid System for Sustainable Energy - Usman, Habib Muhammad; Sharma, Nirma Kumari; Joshi, Deepak Kumar; Kaushik, Aditya; Kumhar, Suraj; Saminu, Sani; Yero, Abdulbasid Bashir (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2024)
Chittorgarh like many other villages in India faces a dual challenge of unreliable electricity supply and heavy dependence on fossil fuels, which undermines economic development and environmental sustainability. Addressing this critical issue, this study explores the optimization of a hybrid grid-connected microgrid comprising wind turbines, solar photovoltaic (PV) systems, and grid integration, aimed at delivering reliable, sustainable, and cost-effective energy. To achieve this, real-world meteorological and energy pricing data were analyzed, and HOMER software was employed for comprehensive system modeling. The proposed microgrid features a 165,024 kW wind turbine system and a 1,500 kW solar PV system, generating a combined annual energy production of 58,772,300 kWh. Wind energy dominates the energy mix, contributing 35,272,200 kWh/year, with a capacity factor of 29%, while solar PV provides 23,500,100 kWh/year with a capacity factor of 22%. Both systems efficiently operate for 4,327 hours/year, supplying a primary AC load of 20,077,351 kWh/year, thereby ensuring reliable energy delivery. Economic analysis reveals that the system's total capital investment is $8.6 million, with replacement and operations and maintenance (O&M) costs amounting to $4.5 million and $3.5 million, respectively. The system demonstrates exceptional economic viability, achieving a Levelized Cost of Energy (LCOE) of $0.0413/kWh, a present worth of $16.6 million, and an annual worth of $1.99 million, delivering a 12% return on investment (ROI). Additionally, the microgrid operates as a net energy exporter, selling 46,979,478 kWh/year to the grid and generating a net annual profit of $53,748, with peak profitability recorded in May ($53,553) and June ($47,615). Sensitivity analysis was conducted under various scenarios, including variations in solar irradiance, wind speed, fuel prices, energy production, and grid prices, to evaluate the robustness of the system's performance and economic metrics. The analysis highlights the resilience of the microgrid design, showcasing its adaptability to diverse operational conditions while maintaining economic and environmental viability. The findings provide compelling evidence for policymakers, investors, and energy stakeholders to adopt renewable energy systems that combine sustainability, reliability, and profitability. By leveraging these insights, similar energy-deficient regions can achieve significant strides toward energy independence and environmental preservation.